Mechanism of Qingdai in Alleviating Acute Lung Injury by Inhibiting the JAK2/STAT3 Signaling Pathway - Qi L; Wang S; Guo T; Qi Z; Wu S; Gao D; Yan Z; Tan B; Yang A (Journal of Inflammation Research)
Lu Qi,1– 3,* Shun Wang,1,3,* Tao Guo,1,3 Zhuocao Qi,1,3 Suwan Wu,1,3 Dan Gao,1,3 Zhiqiang Yan,4 Bo Tan,4 Aidong Yang1,3 1The Research Center for Traditional Chinese Medicine, Shanghai Institute of Infectious Diseases and Biosecurity, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 2The First College of Clinical Medical Science, China Three Gorges University & Yichang Central People’s Hospital, Yichang, 443003, People’s Republic of China; 3School of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 4Laboratory of Clinical Pharmacokinetics, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China*These authors contributed equally to this workCorrespondence: Aidong Yang; Bo Tan, Email aidongy@126.com; tbot@163.comObjective: Qingdai (QD) is a traditional Chinese medicine (TCM) commonly used in clinical practice to treat acute lung injury/acute respiratory distress syndrome (ALI/ARDS). However, the mechanisms underlying the effects of QD remain not fully understood. This investigation demonstrated QD alleviated LPS-induced ALI in mice and exerted anti-inflammatory effects by inhibiting the JAK2/STAT3 signaling pathway.Methods: The active compounds of QD were identified through UPLC-LTQ-Orbitrap-MS/MS. Network pharmacology predicted potential pharmacological targets and the signaling pathways contributed to the effectiveness of QD in treating ALI. Molecular docking assessed the binding of active components to critical targets. ALI mice triggered by Lipopolysaccharides (LPS) were used for transcriptomic analysis to assess alterations in pulmonary gene expression. The pathological changes of lung tissue were analyzed via HE staining. Proinflammatory cytokine levels in serum were measured using ELISA, and the mRNA expression was measured by RT-qPCR. Western blot analysis evaluated protein expression related to the JAK2/STAT3 signaling pathway. Additionally, RAW264.7 cells induced by LPS were treated with QD to measure proinflammatory cytokines and JAK2/STAT3 signaling pathway protein expression.Results: Six major components of QD were identified. Network pharmacology predicted JAK2 and STAT3 as targets for QD in ALI treatment, with KEGG analysis highlighting the JAK/STAT signaling pathway. Transcriptomics confirmed the JAK/STAT signaling pathway in the therapeutic effects of QD. Molecular docking demonstrated high binding affinities of bisindigotin, isoindigo, and 6-(3-oxoindolin-2-ylidene)indolo[2,1-b]quinazolin-12-one (IQO) to JAK2 and STAT3. In vivo, QD reduced lung inflammation, downregulated proinflammatory cytokines, and inhibited JAK2/STAT3 signaling pathway. In vitro, QD mitigated LPS-triggered inflammatory responses in RAW264.7 macrophages by inhibiting the same pathway.Conclusion: The therapeutic effects of QD in ALI might be mediated by the modulation of the JAK2/STAT3 signaling pathway, which may make it a valuable therapeutic strategy for ALI/ARDS. Keywords: Qingdai, acute lung injury, anti-inflammation, macrophages, JAK2/STAT3